Research on the improvement of rural old-age security system in the new era sustainable smart city transportation. (20th May 2021) - Wang, Chenghua; Nagarajan, Senthil Murugan; Anandhan, Prathik
Western digital considers intelligent mobility needs in the present era, so that a harmonious balance is achieved by taking into the consideration of sustainable society, individuals and products which are transported smoothly. The notation of intelligent mobility is aimed at achieving a smooth and sustainable society using the fuzzy linear programming model (FLPM) for notifying communication between carriers fuzzy (NCBCF) and optimisation inter-company in fuzzy (OICF), with a five-layer mobile structure. Finally, this system is used mainly on demand control, supply control, which contributes to the innovation in private and public transportation structure using enhance fuzzy optimisation parametric concept. Further, it supplies the management of urban infrastructure, platform controls, information and the application of transportation for sustainable smart city transportation in an effective and efficient manner.